Имитационные модели систем логического управления в режиме реального времени - Юзовицкий, С. И. (ХНУРЕ, 2019)
Features of logical control systems design and their description language were analyzed. As a model for the description of control systems finite state machines and their modification are considered. It is proposed to use simulation methods to verify the correctness of logical control systems which is operating in real time.